A revision of the southern African species of Polytrichaceae (Musci) - Fanshawe, Nigel Charles (Department of Biological Sciences, 2026)
The last revision of the Southern African Polytrichaceae was by Sim (1926) who described 4 genera and a total of 10 species, one of which, Polytrichum natalense Sim, was proposed as a new species. The type material of Pogonatum borgenii (Hamp.) Jaeg., Polytrichum transvaaliense C.H. and Oligotrichum wageri (Broth.) G. L. Smith was not available to Sim at the time of his revision. Furthermore, Sim described 8 varieties of P.commune L. ex Hedw. as occurring in Southern Africa, two of which were P.commune var. fastigiatum Wils., a very branched form and previously only known from Europe and P.commune var. 'trichodes (C.M) Dix, a form in which the leaves terminate in a long red awn. Sim also reduced the Polytrichum ecklonianum Hamp. to Polytrichum commune var. trichodes (C.H.) Dix. The Southern African representatives of the Polytrichaceae are in need of revision as a result of initial taxonomic errors by Sim, the unavailability of type material to him and subsequent revisions of the family or genera within the family (Kawai 1968, 1969, Nyholm 1969, Smith 1969, 1971, 1974).